HISTORY AND CULTURE: A COMPARATIVE STUDY OF THE ADARA AND ZURU IN KADUNA AND KEBBI STATES FROM THE EARLIEST TIME TO 2018 - MARABS JOSHUA ANTHONY; SOJA ZAKKA (International Studies Journal)
The Adara and Zuru in Kaduna and Kebbi States respectively shared many similarities in their historical trajectory. The historical interconnectedness of these two distinct but historically resembled polities has raised many thoughts in minds as to whether the adara and Zuru were in anyway linked at one point or the other in their historical journey. This work therefore interrogates the fundamental factors that brought these similarities since the earliest time to 2018. In doing the aforementioned, the work will examine the intergroup relations of the diverse but culturally resembled polities of the Adara and Zuru within the context of their origin, nature of their socio-political and cultural links. It will unravel the possible historical melting point of the two nationalities. The work s will use primary (archival records, gazettes, memoirs and oral accounts) and secondary sources (textbooks, newspapers, magazines, articles in journals, online materials, thesis, and dissertations) for data collection, analysis and interpretation. The research will use multiple-group design technique which is expected to conduct many oral interviews across each site of these groups. The composition of the informants will largely be elders from ages fifty and above cutting across both sex (male and female). Since the polities have so much in common in their cultural history, facts from both primary and secondary data that exhibits any form of similarity shall be cross examine and objectively interpreted. At the end, the expected result shall provide the following; trace the origin, migration and settlement pattern of the Adara and Zuru polities, account for the similarities in the nature of the Adara and Zuru socio-political and cultural activities, and examine the possible point of inter-group contact and departure between the Adara and the Zuru.